Cytoplasmic MSH2 immunoreactivity in a patient with Lynch syndrome with an EPCAM–MSH2 fusion. Issue 4 (28th November 2016) - Sekine, Shigeki; Ogawa, Reiko; Saito, Shinya; Ushiama, Mineko; Shida, Dai; Nakajima, Takeshi; Taniguchi, Hirokazu; Hiraoka, Nobuyoshi; Yoshida, Teruhiko; Sugano, Kokichi
Abstract : Aims: Immunohistochemistry for mismatch repair (MMR) proteins is being increasingly used to examine MMR status in tumours. The aim of the present article was to report the case of a colon cancer patient with Lynch syndrome who showed unusual cytoplasmic MMR protein localization. Methods and results: Histologically, the colon cancer was diagnosed as medullary carcinoma associated with prominent tumour‐infiltrating lymphocytes and a Crohn's‐like reaction. Immunohistochemistry revealed cytoplasmic and nuclear expression of MSH2 in non‐neoplastic cells, and exclusively cytoplasmic expression in tumour cells. MSH6 expression was nuclear in non‐neoplastic cells, but was lost in tumour cells. Nuclear expression of MLH1 and PMS2 was retained in both non‐neoplastic and tumour cells. The tumour was microsatellite instability‐high, which is indicative of defective MMR function. A subsequent germline mutation analysis identified a genomic deletion spanning the 3′ region of EPCAM and the 5′ region of MSH2, resulting in an in‐frame fusion of EPCAM and MSH2 . Conclusions: The unusual cytoplasmic immunoreactivity of MSH2 was considered to be attributable to the non‐functional EPCAM–MSH2 fusion product. The present case illustrates that not only loss of expression, but also abnormal localization, of MMR proteins is indicative of a defective MMR system.